Geographical Extension of Free Trade Zones as Trade Liberalization: A Numerical Simulation Approach - Chi-Yung Ng; John Whalley (Center for Economic Studies and ifo Institute (CESifo), 2004)
We consider progressive geographical expansion of free trade zones within countries as a form of trade liberalization and compare observationally equivalent liberalization involving changes in the coverage of a free trade zone for a fixed tariff rate, and tariff reductions applying to all trade if there are no free trade zones in the country (in the sense of generating similar changes in trade volumes). Our work is motivated by China's approach to service trade liberalization in banking and other areas of progressive additions of cities to automatic licence treatment for foreign entities. We use numerical simulation methods to compare conventional national tariff reductions to trade liberalization achieved through the geographical expansion of free trade zones in terms of welfare impacts. Either the size of the free trade zone with a fixed tariff, or the tariff rate given the size of the free trade zone can be endogenously determined so as to yield observational equivalence in the sense of trade volume impacts across trade policy changes. Numerical results overwhelmingly indicate larger welfare costs from imposing geographically restrictive schemes since a higher tariff applies to a smaller fraction of trade, and distortions within country trade also apply. Numerical policy analyses using a conventional tariff-equivalent ad valorem modeling approach to evaluate the impacts of liberalizing geographical barriers can thus be highly misleading. We explore both pure exchange and with production cases, and relate our discussion to earlier literature on free trade zones.
Keywords: 330